Structural Integrity Investigation Of SAC305 Lead Free Solder - Ganiashan, Eesvaran (Universiti Sains Malaysia, 2022)
Improvement in solder strength is instantly becoming one of the most important concerns in the electronics industry, particularly in Printed Circuit Board (PCB) applications. Because of the design and mounting of electronic components on a substrate or PCB, solder in electronic connections may crack and deform to certain factors. These causes device failures and massive costs, and the true impact of crack caused losses in the industrial sector is not widely communicated. As a result, mechanical strength of solder is now one of the most complicated issues, and it has received increased attention in recent years as a result of increased product warranties, advanced technologies, and phase changes brought about by recent laws affecting the electronics sector. In addition, a delicate and unstudied characteristic of SAC305 solder on copper was limited. Therefore, this project was conducted to study the mechanical properties of SAC305 solder. The reflowed SAC305/Cu solder with the temperature of 220℃ at 60 seconds was investigated. The microstructure, structural phase, and hardness of the formed intermetallic compounds were investigated. The interfacial IMC formed between SAC305 and the Cu substrate after solder reflow is Cu6Sn5 and Ag3Sn. The IMCs where visible in SEM and detected in XRD. The effect of IMCs in the terms of hardness was investigated using Vickers hardness test and nanoindentation. A specific indentation array was performed on four different horizontal cross sections of the solder with different heights and diameters. The hardness values increased gradually from the top cross sections towards adjacent to the solder/substrate interface.